3,9-Di-1-naphthyl-2,4,8,10-tetraoxaspiro[5.5]undecane - Xiuqin Zhang; Yuan Cui; Bin Yu; Xiaoqiang Sun; Qiang Chen (Acta Crystallographica Section E, 2010)
In the title compound, C27H24O4, the 1,3-dioxane rings have chair conformations. The molecule has non-crystallographic twofold rotation symmetry. The dihedral angle between the naphthalene ring systems is 17.96(4)° In the crystal structure, weak intermolecular C—H...π interactions contribute to the crystal packing.